Digital Tools Adopted by Public Health Agencies to Support COVID-19 Case Investigation and Contact Tracing, United States, 2020-2021. (November 2022) - Surio, Priyanka; McLean, Jody E.; Jain, Ankur; Chughtai, Zeeshawn; Ruebush, Elizabeth; Lane, J.T.; Ali, Hammad; Pina, Jamie
During the COVID-19 pandemic, public health agencies implemented an array of technologies and digital tools to support case investigation and contact tracing. Beginning in May 2020, the Association of State and Territorial Health Officials compiled information on digital tools used by its membership, which comprises 59 chief health officials from each of the 50 states, 5 US territories, 3 freely associated states, and the District of Columbia. This information was presented online through a publicly available technology and digital tools inventory. We describe the national landscape of digital tools implemented by public health agencies to support functions of the COVID-19 response from May 2020 through May 2021. We also discuss how public health officials and their informatics leadership referenced the information about the digital tools implemented by their peers to guide and refine their own implementation plans. We used a consensus-based approach through monthly discussions with partners to group digital tools into 5 categories: surveillance systems, case investigation, proximity technology/exposure notification, contact tracing, and symptom tracking/monitoring. The most commonly used tools included the National Electronic Disease Surveillance System Base System (NBS), Sara Alert, REDCap, and Maven. Some tools such as NBS, Sara Alert, REDCap, Salesforce, and Microsoft Dynamics were repurposed or adapted for >1 category. Having access to the publicly available technology and digital tools inventory provided public health officials and their informatics leadership with information on what tools other public health agencies were using and aided in decision making as they considered repurposing existing tools or adopting new ones.